2021
DOI: 10.1016/j.tranon.2020.100957
|View full text |Cite
|
Sign up to set email alerts
|

Survival prediction and response to immune checkpoint inhibitors: A prognostic immune signature for hepatocellular carcinoma

Abstract: Highlights As is known to us, this is the first immune-gene-related signature of HCC which was validated in various ways. This signature was linked to the mutation status, and we found the difference of mutation between two risk groups. We estimated the association among the signature, TMB and the survival and found the result contrary to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The IPS was proved to be a predictor of response to checkpoint blockers in patients with melanoma. IPS may serve as a useful tool for evaluating the efficacy of ICIs ( 55 ) and this view was verified in recent study. Furthermore, the close associations of sensitivity to tumor immunotherapy with immune checkpoint genes and tumor immune infiltration ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 56%
“…The IPS was proved to be a predictor of response to checkpoint blockers in patients with melanoma. IPS may serve as a useful tool for evaluating the efficacy of ICIs ( 55 ) and this view was verified in recent study. Furthermore, the close associations of sensitivity to tumor immunotherapy with immune checkpoint genes and tumor immune infiltration ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 56%
“…The relevance of safety for HCC patients was also acknowledged in earlier studies with tyrosine kinase inhibitors, wherein a preliminary endoscopic assessment was considered essential [87][88][89]. As such, attempts to define an immune signature that can help to tailor the best treatment for each subtype are especially welcome and have recently been gaining attention [17,[90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…We further examined the predictive efficacy of immunotherapy in the TCGA cohort. IPS analysis and TIDE analysis were two methods most frequently applied in bioinformatic studies (Wu et al, 2021;Xu R. et al, 2021;Xu Y. et al, 2021;Zhao et al, 2021;Zuo et al, 2021). The IPS analysis results suggested that the SRLncSig might present a better performance in predicting CTLA4 blockade therapy.…”
Section: Discussionmentioning
confidence: 99%